Development and validation of a nomogram for freezing of gait in patients with Parkinson's Disease. (19th January 2022) - Li, Kelu; Zhu, Yongyun; Ning, Pingping; Bao, Jianjian; Liu, Bin; Yang, Hongju; Yin, Weifang; Xu, Yanming; Ren, Hui; Yang, Xinglong
Abstract: Objectives: Freezing of gait (FOG) is a common and complex disabling episodic gait disturbance in patients with Parkinson's disease (PD). Currently, the treatment of FOG remains a challenge for clinicians. The aim of our study was to develop a nomogram for FOG risk based on data collected from Chinese patients with PD. Materials & Methods: A total of 379 PD patients (197 with FOG) from Kunming Medical University were recruited as a training cohort. Additionally, 339 PD patients (166 with FOG) were recruited from West China Hospital of Sichuan University, to serve as the validation cohort. The least absolute shrinkage and selection operator regression model was used to select clinical and demographic characteristics as well as blood markers, which were incorporated into a predictive model using multivariate logistic regression to predict the risk of developing FOG. The model was validated using the validation dataset, and model performance was evaluated using the C‐index, calibration plot, and decision curve analyses. Results: The final predictive model included the REM Sleep Behavior Disorder Screening Questionnaire (RBDSQ) score, Parkinson's Disease Questionnaire (PDQ39), H‐Y stage, and visuospatial function. The model showed good calibration and good discrimination, with a C‐index value of 0.772 against the training cohort and 0.766 against the validation cohort. Decision curve analysis demonstrated the clinical utility of the nomogram. Conclusion: A nomogram incorporating RBDSQ, PDQ39, H‐Y stage, and visuospatial function may reliably predict the risk of FOG in PD patients.